Growing our future: Introducing the Pacific School Food Network to support healthy school food and nutrition environments for better nourished children in the Pacific Islands - Hayman, Ann; Singh, Pragya; Raneri, Jessica Evelyn; Katz, Stefano; Matairakula, Ulamila; MacKay, Clarissa; Horsey, Bridget; Underhill, Steven; Kama, Ateca; Maelaua, Josephine; Demei, Brynn; Mitchell, Arlene; et al. (Elsevier, 2022)
Food systems in the Pacific Islands (P.I.) are transitioning from local, traditional diets to those with low fruit and vegetable intake and largely based on ultra-processed foods that are often, but not always, imported. Alongside changes in diet and health outcomes, there is a loss of traditional and sociocultural dimensions of food, resulting in poor quality diets in many P.I. populations, including children. Besides high rates of overweight and obesity, in some areas stunting rates are up to 48.4%,1 and prevalence of anaemia (5-14 years) as high as 45%.2 After many years of limited multisectoral action and effort to enact sustainable change across policy and practice, there is growing interest in improving school food and nutrition environments (SFE) in the region. Against this backdrop of limited capacity, coordination, effort, research and evidence, the Pacific School Food Network (PSFN) was formed.